The art of veiled speech : self-censorship from Aristophanes to Hobbes - Davis, Peter J.; Baltussen, Han (University of Pennsylvania Press, 2015)
Throughout Western history, there have been those who felt compelled to share a dissenting opinion on public matters, while still hoping to avoid the social, political, and even criminal consequences for exercising free speech. In this collection of fourteen original essays, editors Han Baltussen and Peter J. Davis trace the roots of censorship far beyond its supposed origins in early modern history.Beginning with the ancient Greek concept of parrhêsia, and its Roman equivalent libertas, the contributors to The Art of Veiled Speech examine lesser-known texts from historical periods, some famous for setting the benchmark for free speech, such as fifth-century Athens and republican Rome, and others for censorship, such as early imperial and late antique Rome. Medieval attempts to suppress heresy, the Spanish Inquisition, and the writings of Thomas Hobbes during the Reformation are among the examples chosen to illustrate an explicit link of cultural censorship across time, casting new light on a range of issues: Which circumstances and limits on free speech were in play? What did it mean for someone to "speak up" or "speak truth to authority"?Drawing on poetry, history, drama, and moral and political philosophy the volume demonstrates the many ways that writers over the last 2500 years have used wordplay, innuendo, and other forms of veiled speech to conceal their subversive views, anticipating censorship and making efforts to get around it. The Art of Veiled Speech offers new insights into the ingenious methods of self-censorship to express controversial views, revealing that the human voice cannot be easily silenced.Contributors: Pauline Allen, Han Baltussen, Megan Cassidy-Welch, Peter J. Davis, Andrew Hartwig, Gesine Manuwald, Bronwen Neil, Lara O'Sullivan, Jon Parkin, John Penwill, François Soyer, Marcus Wilson, Ioannis Ziogas.